Приращение функции в точке равно deltaF=F(х0+deltaX)-F(x0)
x0=-2
F(x0)=F(-2)=(-2)^2+2=6
F(x0+deltaX)=F(-2+0.01)=F(-1.99)=(-1.99)^2+2=5.9601
deltaF=5.9601-6=0.0399
я думаю так
<span>А) 4,2x - 1,3 - (1,1 - 1,4x) = 2,6x
4,2х - 1,3 - 1,1 + 1,4х = 2,6х
4,2х + 1,4х - 2,6х = 1,3 + 1,1
3х = 2,4
х = 2,4 : 3
х = 0,8
</span>B) - (5,7 - 2,9x) - (3,8x - 3,7) = - 4,9x
<span>-5,7 + 2,9х - 3,8х + 3,7 = -4,9х
2,9х - 3,8х + 4,9х = 5,7 - 3,7
4х = 2
х = 2 : 4
х = 0,5
</span><span>C) (4,2x + 3,1) - (0,7x - 2,7) = 6,85
</span>4,2х + 3,1 - 0,7х + 2,7 = 6,85
4,2х - 0,7х = 6,85 - 3,1 - 2,7
3,5х = 1,05
х = 1,05 : 3,5
х = 0,3
<span>D) - (2,5x - 2,5) - (3,1x - 3,1) = - (1,6 - 1,6x)
</span>-2,5х + 2,5 - 3,1х + 3,1 = - 1,6 + 1,6х
-2,5х - 3,1х - 1,6х = -2,5 - 3,1 - 1,6
- 7,2х = - 7,2
х = 1
<span>E) (3,1x + 3,1) - (1,8x + 1,8) = 1,6x + 1,6
</span>3,1х + 3,1 - 1,8х - 1,8 = 1,6х + 1,6
3,1х - 1,8х - 1,6х = - 3,1 + 1,8 +1,6
- 0,3х = 0,3
х = - 0,3 : 0,3
х = - 1